The linkage between the education and employment systems: Ideal types of vocational education and training programs - Ladina Rageth; Ursula Renold (ETH Zurich, KOF Swiss Economic Institute, 2017)
In this article, we argue that every typology should be constructed in a systematic, transparent process. Moreover, to validate a typology's explanatory value, a typological approach must rest on a strong theoretical foundation. We both propose such an approach and apply it to construct three ideal types of vocational education and training (VET) programs. We build on Luhmann's theory of social systems, which helps elucidate the significance of the linkage between actors from the education and employment systems in VET. The first ideal type, with a maximal linkage, entails equal power-sharing between actors from the two systems. We expect such a VET program to have the most favorable youth labor market outcome. In contrast, the other two ideal types, in which only one system has all of the power, result in either undesirable outcomes, such as unemployment or skill mismatch, or missing access to further education.
Keywords: 330; Vocational Education and Training; Education System; Social Systems Theory; Typology